FLANE as a strategy in educating mothers its effect on the nutritional status of preschool children - Talavera, Ma. Theresa M.
This study examined the following: 1) effectiveness of using games and exercises in educating mothers on the prevention of micronutrient malnutrition; 2) the fators that could influence the knowledge, attitudes and practices of mothers; 3) relationship between an increase in knowledge, attitudes and practices of mothers and improvement in the nutritional status of preschool children; and 4) two approaches of conducting FLANE NUT ED class, two consecutive days or three times a week.Sixty-three (63) mothers were assigned to three groups (group 1 - no FLANE NUT ED class, grou 2 attended a two-day FLANE NUT ED class, and group 3 attended a three times a week FLANE NUT ED class). Mothers were interviewed before and after the FLANE NUT ED class. After the FLANE NUT ED class, fourteen (14) mothers were observed for 2 weeks (3 months after and 6 months after the FLANE NUT ED was conducted) to determine whether or not the behaviors promoted were praticed. In addition, the weight of preschool children were measured three times: 1) before the FLANE NUT ED class, 2) three months after and 3) 6 months after the FLANE NUT ED class.Results showed that the FLANE NUT ED class was effective in increasing knowledge, attitudes and practices on micronutrient malnutrition of mothers in the experimental groups. Mothers in group 3 had the highest mean posttest score in knowledge, practice and total KAP score followed by group 2; but group 2 had the highest mean posttest attitude score. However, results of the analysis of variance showed that there was no significant difference found between the two experimental groups. Thus, either of the two approaches can be used in conducting the FLANE NUT ED class.The factors found to be significantly and positively correlated with total KAP score was attendance to FLANE NUT ED class; the knowledge score was found to be significantly and positively correlated with attendance to FLANE NUT ED class and number of FLANE sessions attended. Attendance to FLANE NUT ED class and income of mother were factors found to influence the knowledge score of mothers.Educational attainment was the only factor found to be significantly and positively correlated with the mothers' attitude score of mothers. The same factor was found to influence the attitude score together with age and income of husband. On the other hand, the practice score was found to be significantly and positively correlated with attendance to FLANE NUT ED class and number of FLANE sessions attended. A significant but negative correlation was found between the posttest practice score and total income and income of husband.Lastly, improvements in the nutritional status of preschool children were evident for all groups but group 3 had the highest proportion of preschool children with improved weights. However, the improvements were found not to be significant. Moreover, there was no relationship found between the improvements in the knowledge, attitudes, and practices of mothers and the nutritional status of preschool children. Thus, nutrition education alone cannot lead to an improvement in the nutritional status of preschool children.